Intraindividual reaction time variability is malleable: feedback- and education-related reductions in variability with age - Garrett, Douglas D.; MacDonald, Stuart W.; Craik, Fergus I. (Frontiers in Human Neuroscience, 2012)
Intraindividual variability (IIV) in trial-to-trial reaction time is a robust and stable within-person marker of aging. However, it remains unknown whether IIV can be modulated experimentally. In a sample of healthy younger and older adults, we examined the effects of motivation- and performance-based feedback, age, and education level on IIV in a choice RT task (four blocks over 15 minutes). We found that IIV was reduced with block-by-block feedback, particularly for highly educated older adults. Notably, the baseline difference in IIV levels between this group and the young adults was reduced by 50%; by the final testing block, this advantaged older group had improved such that they were statistically indistinguishable from young adults on two of three preceding testing blocks. Our findings confirmed that response IIV is indeed modifiable, within mere minutes of feedback and testing.